2002
DOI: 10.1074/jbc.m200769200
|View full text |Cite
|
Sign up to set email alerts
|

BARD1 Induces BRCA1 Intranuclear Foci Formation by Increasing RING-dependent BRCA1 Nuclear Import and Inhibiting BRCA1 Nuclear Export

Abstract: BRCA1 is a tumor suppressor with several important nuclear functions. BRCA1 has no known cytoplasmic functions. We show here that the two previously identified nuclear localization signals (NLSs) are insufficient for nuclear localization of BRCA1 due to the opposing action of an NH 2 -terminal nuclear export signal. In transfected breast cancer cells, BRCA1 nuclear localization requires both the NLSs and NH 2 -terminal RING domain region; mutating either of these sequences shifts BRCA1 to the cytoplasm. The BR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
202
1
4

Year Published

2003
2003
2011
2011

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 175 publications
(219 citation statements)
references
References 51 publications
12
202
1
4
Order By: Relevance
“…Asynchronous MCF-7 cells, hydroxyurea (HU; early S phase blocker) and nocodazole (G 2 /M blocker)-treated cells were fixed and fluorescently stained for both cyclin D1 and BRCA1 proteins (Figure 2). BRCA1 was detected in both the nucleus and cytoplasm of untreated cells, previously reported for MCF-7 cells (Fabbro et al, 2002). Cyclin D1 staining was also found in both the cytoplasm and nucleus (Figure 2, untreated cells).…”
Section: Cyclin D1 and Brca1 Colocalizesupporting
confidence: 79%
“…Asynchronous MCF-7 cells, hydroxyurea (HU; early S phase blocker) and nocodazole (G 2 /M blocker)-treated cells were fixed and fluorescently stained for both cyclin D1 and BRCA1 proteins (Figure 2). BRCA1 was detected in both the nucleus and cytoplasm of untreated cells, previously reported for MCF-7 cells (Fabbro et al, 2002). Cyclin D1 staining was also found in both the cytoplasm and nucleus (Figure 2, untreated cells).…”
Section: Cyclin D1 and Brca1 Colocalizesupporting
confidence: 79%
“…Another study suggests that BARD1 may also act to facilitate nuclear entry of BRCA1 and block its exit (by covering up the BRCA1 nuclear export signal) (Fabbro et al, 2002). It has been suggested that the ubiquitin protein ligase activity of the BRCA1/BARD1 contributes to many of the biologic functions of the BRCA1 protein, including its breast and ovarian cancer suppressor activity (Baer and Ludwig, 2002).…”
Section: Brca1 Regulation Of the Proteomementioning
confidence: 99%
“…Interaction with importin α can occur through two nuclear localization signals in BRCA1 located at amino acids 503-508 and 606-615 [14], but studies suggest that only the interaction at amino acid residues 503-508 is physiologically important in targeting BRCA1 to the nucleus [15]. The interaction of BARD1 with BRCA1 also results in the translocation of BRCA1 into the nucleus via a piggyback mechanism [16,17]. The nuclear export of BRCA1 occurs via two leucine-rich nuclear export sequences located at amino acid residues 81-99 [17] and 22-30 [18].…”
Section: Introductionmentioning
confidence: 99%